2021
DOI: 10.31729/jnma.5636
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Obesity in Inguinal Hernia Repair Patients in a Tertiary Care Center

Abstract: Introduction: Inguinal hernia is a common surgical problem, with a lifetime risk of 27% in men and 3% in women. Its cumulative incidence is 17.2% and 12.3% in body mass index of <25 kg/m2 and 25–30 kg/m2 respectively. Obesity had been regarded as the risk factor for the development of an inguinal hernia. However, recent epidemiologic studies have suggested the decreased prevalence of inguinal hernia in increased weight and body mass index individuals. The aim of this study is to find out the prevalence of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
6
0
1
Order By: Relevance
“…We also demonstrated that normal body mass index (BMI<24 kg/m 2 ) was inversely related to the formation of inguinal hernia, which has been reported in many previous studies. 39 - 41 While EFEMP1 locus has been associated with anthropometric measures of body height and abdominal circumference, shared genetic effects may explain the plausible causality between BMI and inguinal hernia, as previously noted by Hélène Choquet et al 20 However, further investigation of different pathophysiological associations of EFEMP1 in sex-specific manner may be considered as opposite correlations between EFEMP1 rs2009262 TC/CC and inguinal hernia were observed in different genders according to BMI levels.…”
Section: Discussionmentioning
confidence: 81%
“…We also demonstrated that normal body mass index (BMI<24 kg/m 2 ) was inversely related to the formation of inguinal hernia, which has been reported in many previous studies. 39 - 41 While EFEMP1 locus has been associated with anthropometric measures of body height and abdominal circumference, shared genetic effects may explain the plausible causality between BMI and inguinal hernia, as previously noted by Hélène Choquet et al 20 However, further investigation of different pathophysiological associations of EFEMP1 in sex-specific manner may be considered as opposite correlations between EFEMP1 rs2009262 TC/CC and inguinal hernia were observed in different genders according to BMI levels.…”
Section: Discussionmentioning
confidence: 81%
“…Multiple studies have shown that, however, an increased BMI actually involved a decreased risk of developing inguinal hernia. The occurrence of inguinal hernia was associated with normal rather than low or high values of the BMI (24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Methodsmentioning
confidence: 88%
“…For example, some studies have shown that overweight and obese patients are more likely to develop recurrent hernias, hence the surgeons must be aware of their risk and these patients need a proper follow-up and a careful monitoring (28). However, other studies deny this correlation, stating that the outcomes of the surgery are not significantly different among obese patients: neither the recurrence risk, nor the complications increase with the BMI (29,24,33). Nonetheless, some difficulties, such as the increased risk of surgical site infections (24,34) or the increased operative time (30) might arise when performing surgery on obese patients.…”
Section: Methodsmentioning
confidence: 99%
“…When determining the risk of developing the above complications, the main role is given to the quality of the surgical intervention, the strict adherence to the methodology of the surgical support both in open and laparoscopic operations [21,22]. At the same time, the role of common factors independent of the surgical technique is recognized, primarily the age of the patient and the concomitant pathological conditions, including obesity [23][24][25][26]. The question of the preference for one or another approach to hernioplasty, if available, doesn't appear to have been finally resolved in the meantime.…”
Section: вестник хирургии казахстана №1 2023mentioning
confidence: 99%